2012
DOI: 10.1007/s00402-012-1488-5
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of the effect of corticosteroids and platelet-rich plasma (PRP) for the treatment of plantar fasciitis

Abstract: Our results revealed that both methods were effective and successful in treating plantar fasciitis. When the potential complication of corticosteroid treatment was taken into consideration, PRP injection seems to be safer and at least having same effectivity in the treatment of plantar fasciitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
134
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(150 citation statements)
references
References 21 publications
(28 reference statements)
9
134
2
5
Order By: Relevance
“…[8] Two studies compared corticosteroid injection with platelet-rich plasma injections. [9,11] One study compared corticosteroid injection with NSAID (tenoxicam) injection. [10] one study compared corticosteroid injection with PRP and placebo injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Two studies compared corticosteroid injection with platelet-rich plasma injections. [9,11] One study compared corticosteroid injection with NSAID (tenoxicam) injection. [10] one study compared corticosteroid injection with PRP and placebo injection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the effectiveness of joint mobilization combined with stretching exercises v/s steroid injection in the treatment of plantar fasciitis [13] demonstrated that steroid injection gives better relieve but only for a short term whereas exercises give improvement in disability longer periods. To rule out confounding effect of exercises on the results as noted in some studies [11] , in our study both the groups patients were given common supportive measures such as soft heel and advised same stretching exercises and common precautions such as not walking bare foot and standing for long durations. NSAIDs mainly act by inhibition of prostaglandin synthesis, but they do not suppress the production of other inflammatory mediators like leukotrienes, cytokines, platelet activating factor etc.…”
Section: Discussionmentioning
confidence: 99%
“…En un periodo de seis meses, la mejora fue estadística-mente significativa en los síntomas, sin encontrar diferencias entre ambos grupos. Los autores, considerando los riesgos y efectos adversos de los corticoides, prefieren el uso de las PRP 50 . No existen estudios comparativos entre las PRP y la microtenotomía por Radiofrecuencia.…”
Section: Faseunclassified
“…6,7 NICE has also approved Extracorporeal Shockwave Therapy (ESWT) for the treatment of intractable plantar fasciitis with encouraging results.…”
Section: Treatmentmentioning
confidence: 99%